A Rare Complication of Thymoma: Pure White Cell Aplasia in Good's Syndrome. (13th October 2019) - Uy, Kim; Levin, Elizabeth; Mroz, Pawel; Li, Faqian; Shah, Surbhi
Abstract : Pure white cell aplasia (PWCA) is a rare manifestation of thymoma. It is characterized by agranulocytosis with absent myeloid precursors in the bone marrow and normal hematopoiesis for other cell lines. Here we describe a 65-year-old female patient who presented with three days of fever and night sweat. Chest CT revealed an anterior mediastinal mass. A biopsy of the mass confirmed a diagnosis of thymoma mixed type A and B2. The patient developed a severe neutropenia, and her bone marrow revealed significantly decreased neutrophil-lineage cells, rare to absent B cells, and defective T cells, consistent with PWCA. Following thymectomy, a complete resolution of PWCA was achieved via multimodality therapy of intravenous immunoglobulins, granulocyte colony-stimulating factor, and immunosuppressant. This report highlights the care complexity regarding treatment choices and decision to perform thymectomy in patients presenting with PWCA.